2022
DOI: 10.1002/app.52797
|View full text |Cite
|
Sign up to set email alerts
|

Stretchable, conductive poly(acrylamide‐co‐maleic acid)/triethylene glycol/NaCl double‐crosslinked organohydrogel with excellent antifreezing and sensing properties

Abstract: Recently, the wearable electronic devices have attracted extensive attention while the low stretchability and freezing-induced performance deterioration largely limit the applications in many fields. In this work, the poly(acrylamide-co-maleic acid) hydrogels are immersed in the triethylene glycol/sodium chloride/water solution to establish the dual-crosslinked organohydrogels, which present the extraordinary stretchability (1322 ± 75%) ascribed to the energy dissipation of physical interactions and stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The gauge factor (GF) of is estimated by eq : , GF = false( R R 0 false) / false( R 0 ε false) where ε was the applied strain.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The gauge factor (GF) of is estimated by eq : , GF = false( R R 0 false) / false( R 0 ε false) where ε was the applied strain.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Wang, Lai, Li, and Wu et al reported a ionic conductive hydrogel ( Figure 6 A), which was a dual-crosslinked organohydrogel fabricated by immersing the poly(acrylamide-co-maleicacid) hydrogels in triethylene glycol/sodium chloride/water solution with electrical conductivity and excellent stretchability (1322 ± 75%), even at low temperature [ 44 ]. Sun and He et al reported a ionic zwitterionic nano-micelle hydrogel, which was fabricated via in situ co-polymerization of zwitterionic monomer SBMA and nonionic monomer-hydroxyethyl methacrylate (HEMA) using Pluronic F127 di-acrylate (F127DA) as macro-crosslinkers ( Figure 6 B) [ 45 ].…”
Section: Principles Of Hydrogelmentioning
confidence: 99%
“… ( A ) Schematic illustration of ionic conductive hydrogels’ formation, structure, and intermolecular interactions. Reproduced with permission from Wiley-VCH, copyright 2022 [ 44 ]. ( B ) Schematic illustration of the fabrication process of the nano-micelle zwitterionic hydrogels.…”
Section: Figurementioning
confidence: 99%